Peran Pustakawan dalam Inovasi Pengembangan Koleksi Digital: (Studi Kasus di Dinas Perpustakaan dan Kearsipan Tulungagung) - Heylen Amildha Yanuarita; Djoko Susanto; Satriyani Cahyo Widayati (Universitas 17 Agustus 1945, 2025)
The advancement of information and communication technology has significantly transformed library management, shifting from print-based services to digital-based platforms. This transformation requires librarians to move beyond their traditional role as collection managers to become agents of innovation who connect community information needs with technological developments. This study aims to examine the contribution of librarians’ roles in fostering innovation using Soerjono Soekanto’s (2002) role theory, which encompasses three dimensions: normative, ideal, and actual. Employing a descriptive qualitative approach, data were collected through interviews, observations, and documentation, and analyzed using reduction, presentation, and conclusion drawing techniques. The findings indicate that librarians carry out normative roles through compliance with regulations, digitization standards, metadata, and copyright; ideal roles as digital transformation agents, local collection developers, information technology experts, and digital literacy educators; and actual roles through digitization practices, metadata input, user assistance, and SOP-based services. The results demonstrate that librarians play a strategic role in advancing digital collection development, both through professional compliance and through creative and adaptive engagement with technology. Consequently, librarians strengthen regional libraries as centers of literacy, cultural preservation, and trusted information in the digital era. The novelty of this research lies in integrating Soerjono Soekanto’s role theory into the context of digital library transformation, thereby offering a new analytical framework that positions librarians not merely as technical executors but as strategic actors in regional information service innovation.